Nexus between climate change and agricultural outputs in China - Sikwela, Misery Mpuzu; Aderemi, Timothy Ayomitunde; Ntshangase, Bhekabantu Alson; Ramsarghey, Kevin (Asian Development Policy Review, 2025)
In recent years, China has experienced higher warming than the global average, making the country more susceptible to the climate change crisis. This study investigates the relationship between climate change and agricultural outputs in China from 1990 to 2020. The analysis of climate change’s influence on Chinese agricultural outputs was conducted using dynamic ordinary least squares. The findings indicate that access to the internet (LNATI) shows a non-significant negative relationship, while access to electricity (LNATE) positively impacts agricultural output. Higher carbon emissions (LNCO2) are associated with decreased agricultural productivity, emphasizing the importance of environmental sustainability. Changes in rainfall patterns (LNCRP) exhibit a negative trend without statistical significance, suggesting potential long-term implications. Conversely, trade openness (LNTO) demonstrates a significant positive correlation, highlighting the benefits of international trade. The high R-squared and adjusted R-squared values underscore the model’s effectiveness in explaining variations in agricultural output. The study recommends that the Chinese government prioritize climate resilience and carbon emission reduction in agriculture. Strategies include promoting adaptive practices, reducing emissions, and fostering innovation for sustainable development amid climate change.